Anti-atherosclerosis effect of H2S donors based on nicotinic acid and chlorfibrate structures. Issue 15 (1st August 2019) - Bai, Zhongjie; Zhang, Jinlong; Zhang, Qiuping; Wang, Yanni; Li, Jili; Zhao, Quanyi; Wang, Zhen; He, Dian; Zhang, Jingke; Liu, Bin
Graphical abstract: Highlights: Firstly, based on the structures of nicotinic acid and chlorfibrate, a series of new H2 S donors were synthesized. Investigate the protective effects of HUVEC cells damaged by ox-LDL and the inhibition of foam cell formation. Explore the synergistic effect of lipid lowering drugs and H2 S donors. Abstract: Based on the structures of nicotinic acid and chlorfibrate, a series of new H2 S donors were synthesized and their anti-atherosclerosis activities using Ox-LDL RAW 264.6 cells as model were evaluated. The release test showed that all the compounds could release H2 S effectively and showed low cytotoxicity. In the bioactivity experiments, compounds1, 3, 9 and14 increased the survival rate of HUVEC cells treated by ox-LDL; among four compounds, compounds1 and3 displayed higher activity than the others. In the foam cell model, compounds1 and3 were found to inhibit the formation of foam cells and significantly reduced the content of TC and FC in foam cells. They had more obvious effects on lipid reduction than those of nicotinic acid and chlorfibrate. In anti-oxidation, compounds1 and3 significantly reduced ROS and MDA and increased the expression level of SOD, whereas the precursor compounds, niacin and chlorfibrate had little antioxidant effect. In addition, both compounds also inhibited the inflammatory response in foam cells, with reducing pro-inflammatory factor TNF-α and increasing anti-inflammatory cytokine IL-10. WB assay showed that the tested compounds inhibited the expression levels PI3K, Akt and NF-κb proteins. In conclusion, the compounds as H2 S donors could protect HUVEC cells from damage and inhibit the formation of foam cells by inhibiting PI3K/Akt/NF-κb signal pathway. All these suggest the compounds have potential to be candidate for anti-atherosclerosis medicines.